Effects of the Pt Shell Thickness on the Oxygen Reduction Reaction on a Well‐Defined Pd@Pt Core‐Shell Model Surface. Issue 1 (17th October 2022) - Hashiguchi, Yuta; Nakamura, Isao; Honma, Tetsuo; Matsushita, Toshiyuki; Murayama, Haruno; Tokunaga, Makoto; Choe, Yoong‐Kee; Fujitani, Tadahiro
Abstract: The effect of the Pt shell thickness on the oxygen reduction reaction (ORR) of a Pd@Pt core‐shell catalyst was studied using surface science technics and computational approaches. We found Pt shells on Pd rods to be negatively charged because of charge transfer from the Pd substrate when the shell thicknesses were 0.5 or 1 monolayer (ML). The activities of the ORR of the model surface with a Pt shell of 0.5 or 1 ML were similar and more than twice the activities of a Pt/C or Pt rod. The relationship between the ORR activity and the thickness of the Pt shell was the exact opposite of the relationship between the Pt binding energy and the Pt shell thickness. The indication was that more negatively charged Pt had higher ORR activity. Density functional theory calculations confirmed that a single layer of Pt atoms located on Pd was negatively charged compared to pure Pt and resulted in a lower barrier to the rate‐limiting step of the ORR. Abstract : Pt@Pd core‐shell catalysts containing a single shell layer show a better catalytic performance because the top Pt layer atoms located over the Pd atoms are more negatively charged than pure Pt, which lowers the barrier to the rate‐limiting step of the oxygen reduction reaction.